Microgravity triggers ferroptosis and accelerates senescence in the MG-63 cell model of osteoblastic cells - Nancy Garbacki; Jérôme Willems; Thibaut Neutelings; Charles Lambert; Christophe Deroanne; Astrid Adrian; Markus Franz; Matthias Maurer; Philippe De Gieter; Betty Nusgens; Alain Colige (npj Microgravity, 2023)
Abstract In space, cells sustain strong modifications of their mechanical environment. Mechanosensitive molecules at the cell membrane regulate mechanotransduction pathways that induce adaptive responses through the regulation of gene expression, post-translational modifications, protein interactions or intracellular trafficking, among others. In the current study, human osteoblastic cells were cultured on the ISS in microgravity and at 1 g in a centrifuge, as onboard controls. RNAseq analyses showed that microgravity inhibits cell proliferation and DNA repair, stimulates inflammatory pathways and induces ferroptosis and senescence, two pathways related to ageing. Morphological hallmarks of senescence, such as reduced nuclear size and changes in chromatin architecture, proliferation marker distribution, tubulin acetylation and lysosomal transport were identified by immunofluorescence microscopy, reinforcing the hypothesis of induction of cell senescence in microgravity during space flight. These processes could be attributed, at least in part, to the regulation of YAP1 and its downstream effectors NUPR1 and CKAP2L.